PARENTS PARTICIPATION IN CHILDREN DAY CENTRE ACTIVITIES: THE PERSPECTIVE OF THE SOCIAL WORKER - Klokmanienė, Loreta; Rimkuvienė, Audronė; Janiselienė, Inga (PROFESSIONAL STUDIES: Theory And Practice, 2022)
One of the most vulnerable groups in society is children who due to their age, are unable to take care of themselves, so their rights must be taken care of at national level. For children who face a certain social risk because of circumstances of life in which the conditions for their successful education are not fully ensured, appropriate conditions are created in children's day care centers. The aim is to analyze the attitude of social workers to the participation of parents in the activities of the children's day center. The article on the basis of the data of qualitative research presents the experience of social workers working in the children's day care center and the involvement of parents in the activities of the children's day care center. Seven social workers working in Catholic children’s day care centers were selected for the research. The results of the research revealed that in children's day care centers, social workers provide various services to children and their parents, including socio-cultural, lesson preparation, social skills development, individual and group counseling, work skills development, and free meals. Parents' participation in children's day care centers is very important, as their values change, new and improved social skills are acquired, communication and creative skills are revealed, they learn to deal with material difficulties, and responsibility for one's children and family is strengthened. Key words: children day center, a child, social skills, empowerment.